Evaluation of the beef marbling insurance theory - Drey, Lindsey (Kansas State University, 2018)
The objectives of this study were to evaluate the extent marbling compensates for reduced beef palatability at elevated degrees of doneness and to determine the relationship of residual moisture and fat in cooked steaks to beef palatability, specifically beef juiciness. Paired strip loins (IMPS # 180) were collected to equally represent five quality treatments [Prime, Top Choice (modest and moderate marbling), Low Choice, Select, and Select Enhanced (110% of raw weight)]. Steaks were grouped into sets of three consecutively cut steaks and randomly assigned a degree of doneness (DOD): very-rare (VR; 55°C), rare (R; 60°C), medium-rare (MR; 63°C), medium (M; 71°C), well-done (WD; 77°C), or very well-done (VWD; 82°C). Samples were subjected to consumer and trained sensory evaluation, Warner-Braztler shear force (WBSF), slice shear force (SSF), pressed juice percentage (PJP) evaluation, and raw and cooked proximate analysis. There were no (P > 0.05) interactions for consumer sensory ratings, indicating increased DOD had the same negative impact regardless of marbling level. There was a quality treatment × DOD interaction (P < 0.05) for percentage of steaks rated acceptable by consumers for juiciness. Increased marbling extended the point in which steaks became unacceptable for juiciness. Similarly, there was a quality treatment × DOD interaction (P < 0.05) for trained juiciness ratings. When cooked to MR and lower, Prime was only rated 8 to 18% higher (P < 0.05) than Select for trained juiciness ratings but was rated 38 to 123% higher (P < 0.05) than Select when cooked to M and higher. Besides cook loss, combined cooked moisture and fat percentage was more highly associated (P < 0.01) to consumer juiciness (r = 0.69) and trained initial (r = 0.84) and sustained (r = 0.85) juiciness ratings than all other objective evaluations. For regression analysis, cooked moisture and fat percentages, alone, were poor indicators of consumer and trained juiciness ratings. However, when combined, the regression equations explained 45, 74, and 69% of the variation in consumer, trained initial, and trained sustained juiciness ratings, respectively. These results indicate that increased marbling levels only offer “insurance” for juiciness of steaks that are cooked at high degrees of doneness, but not for other palatability traits. Additionally, cooked residual moisture and fat percentages when combined are a good indicator of sensory juiciness ratings.
Keywords: Beef; Marbling; Degree of Doneness; Juiciness; Cooked Proximates